Analisis Penerapan Manajemen Risiko Pembiayaan Pada BMT Al-Furqan - Alfian, Annisa Maulidia; Nurwahidin; Hannase, Mulawarman; Alfian (Journal of Islamic Management, 2024)
This research aims to analyze the application of risk management in customer business financing provided by BMT al-Furqan. The problem in this research is that risk management has not been implemented well because there is no special team or division to manage the possible risks. This research uses risk management theory. The data collection method was conducted through interviews and a report document, and the data analysis used a qualitative risk assessment. The thing that distinguishes this research from previous research is the risk indicator. This research adds a risk indicator for customer error in carrying out the contract agreement. The study results show five risk indicators in the acceptable category, eight in the undesirable category, and one in the unacceptable category. The suggestion for BMT Al-Furqan, it is necessary to create standardization and special methods for analyzing customers, also use the 5C analysis method. BMT Al-Furqan needs to provide sheets for monitoring and evaluation so that customers can be controlled. BMT also needs to provide a special team to manage risk management. If a problem occurs, it can be detected early.